WRITTEN CODE SWITCHING: THE CASE OF INDONESIAN EMAIL USERS - Nani Hizriani (LET: Linguistics, Literature and English Teaching Journal, 2012)
This study aims at describing code switching found in Indonesian email users among Indonesian speakers living in Australia with a specific setting in Ramadan and Idul Fitri. It focuses on the analysis of the types, the functions and the reasons why Indonesian students in Australia switch their language. The research problems are what types of code switching  Indonesian writers use,  the functions of code switching used by Indonesian writers and why Indonesian writers use these particular code switching.   This study is expected to make some useful contributions the study of written code switching which had little research to date. Another benefit is that, this study gives an insight into how language competence develops under second language environmental influence. Moreover, this might lead to a better understanding of the use of code switching, especially in the emerging genre of Internet communication.